Synthesis of molten salt as heat transfer fluid for waste heat recovery application - Mohamad Redzuan, Nurul Adila (2015)
Basically, various materials such as water, oil heat, ionic liquids and also molten salt are selected to serve as heat transfer fluid. The properties of the different heat transfer fluid determine their performance in any application. The development of nitrate molten salt with different constituent salt are studied to characterize the physical and thermal properties based on low melting point and high thermal stability in order to be considered as heat transfer fluid in waste heat recovery applications. The nitrate based molten salt that has been use in this study consists of binary, ternary and quaternary salt mixture with different weight composition. Molten salt mixture has been dried in the furnace for 12 hours before mixing. After mixing, the salt mixture was heated in furnace at 150 ºC for 4 hours and increased the temperature to 400 ºC for 8 hours for homogenize the salt mixture. The temperature was reduced to 115 ºC for 1 hour before removed from furnace. Thermal analyses were performed using differential thermal analysis (DTA), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). These analyses were conducted to obtain the melting point, thermal stability and heat capacity of molten salt and fulfill the targeted characteristic of a heat transfer fluid. The result shows the melting point for ternary and quaternary mixtures are closely 100 ºC where the value is 92.4 ºC and 98.9 ºC compared than binary mixtures. Thermal stability analyzed in this study shows that the value for all mixture above 500 ºC but quaternary mixture showed the highest thermal stability which the value is 701 ºC. For heat capacity value of all mixture shows a range between 2.5 – 4.7 J/g ºC and quaternary mixture showed the highest value of heat capacity when compared to all mixture with value of 4.7 J/g ºC. For the conclusion, the quaternary salt mixture has fulfilled the targeted characteristic as heat transfer fluid with low melting point, high thermal stability and heat capacity.